New York - Maine, Tyler (North Mankato, Minnesota Capstone Press, a capstone imprint, 2017)
"This book uses maps, full color photographs, and easy-to-read text to introduce the state of New York"--
Different countries
Includes bibliographical references and index
Grades 4-6
Ages 8-10
1 2 13
Keywords: New York (State) -- Juvenile literature